Oxygen Systems in Indonesian Hospitals: Cross- Sectional Study and Strengthening Roadmap - Meliala, Andreasta; Olivia Frans, Sandra; Hidayah, Widy; Nurfadillah, Siti; Rarasati, Srimurni; Nisa, Iztihadun; Krautmann, Michael; Magnanni, Robert (Indonesian Association for Public Administration, 2025)
Medical oxygen is a life-saving medicine essential to modern healthcare; however, ensuring its availability remains a critical policy challenge in low- and middle-income countries. Weaknesses in production, distribution, and preparedness often translate into inequities in access, while the COVID-19 pandemic demonstrated how governance and logistical failures can rapidly escalate into a national emergency. This study aimed to assess the oxygen system readiness in Indonesian hospitals and highlight priority gaps for reform. A cross-sectional survey was conducted in 2022 across 96 hospitals in 18 districts across five provinces. Using an adapted WHO Biomedical Equipment for COVID-19 Case Management Inventory, seven domains of oxygen readiness were evaluated: oxygen source, distribution, regulation, delivery, monitoring, power supply, and maintenance. Findings revealed that only 65% of hospitals had a complete oxygen system, with better readiness among hospitals on Java, public hospitals, and higher-class facilities (A and B). Significant disparities persist, particularly among referral hospitals outside Java and among lower-class hospitals. This study underscores the importance of embedding oxygen management explicitly into health system reform and governance frameworks. Strengthening oxygen supply mechanisms offers practical and managerial opportunities to enhance resilience, equity, and preparedness for future health emergencies.